Cinema e educação feminina: uma análise do filme “Capitã Marvel” - CORRÊA, Eliane Melo (2024)
The aim of this paper is to analyze the film Captain Marvel and discuss cinema and female education. We seek to reflect on how the media reproduce stereotypes, such as cinema, which has historically been centered on white men, reflecting a patriarchal society. This research features scenes from the film, which are analyzed based on screen ethnography, by cutting out scenes in which it is possible to identify issues of gender and empowerment. We also tried to relate the issues presented to the present day and the discussions involving the participation of women in spaces considered to be mostly male. When the heroine Carol Danvers arrives in theaters as the protagonist, she contributes to questioning certain social representations. This is important so that girls can see themselves as protagonists, having this reference, and so that boys have the opportunity to see other representations, breaking the stereotypes of stories that always place men as the main characters and holders of strength, while women are portrayed as submissive and weak.